Investigation of Alardinskaya mine coal bumps causes using computer simulation of rock massif stress conditionals - Sidorenko Andrey (EDP Sciences, 2021)
The purpose of the paper was to identify the causes of rock bumps that occurred at the Alardinskaya mine (Russia) in 2011. The research was carried out using the finite element method. The developed three-dimensional model of the rock mass included a coal seam, rocks bedding above and below, goaf, and a system of local preparatory workings. The situation that arose immediately before the first rock burst was modeled during the research - when the longwall crossed a diagonal entry. The performed investigations enabled the authors to make a conclusion about a high danger of using technological schemes for the development of seams by longwalls leaving pillars that have a width less than the length of the support pressure zone, especially due to diagonal entries. As a safe technology for the longwall development of seams prone to rock bursts, it is recommended to apply a technological scheme with the abandonment of wide barrier pillars and four preparatory workings in each section, which has proven itself in the processing of rock bump hazardous seams in the state of Utah (USA).